Transient control of DFIG-based wind power plants in compliance with the australian grid code - Mohseni, M.; Islam, Syed (2012)
Australian Grid Code has recently enforced stringent regulations on the transient response of large wind power plants (WPPs). The new grid code requires wind generators to ride-through severe low- and high-voltage conditions, provides reactive power support during the fault period, and exhibits fast power recovery after the supply voltage restoration. This paper proposes a new control scheme for doubly fed induction generator (DFIG)-based WPPs to fulfill these requirements in one inclusive approach. New design strategies for the outer power control loops of DFIG are suggested and their corresponding P-Q capability curves are rigorously studied. It is shown that safely overloaded converters can enhance the reactive power capability of DFIGs during the fault periods. Moreover, for the inner current control loops, the conventional PI current regulators are replaced with enhanced hysteresis-based current regulators. This current regulator, with very fast transient response, increases low- and high-voltage ride-through capabilities of the DFIG, as requested by the Australian Grid Code. Finally, time-domain simulation studies are conducted to evaluate the capability of the proposed control scheme to fulfill the Australian regulations and examine its positive impacts on the transient response of the adjacent fixed-speed WPP. © 2006 IEEE.